Avaliação das condições química e física dos sedimentos do estuário Jundiaí-Potengi - Medeiros, Rina Lourena da Silva (2009)
The aim of this study was to quantify the presence of major and minor elements in the sediments of the Jundiaí-Potengi estuary, bordering the municipalities of Macaíba, Natal and São Gonçalo do Amarante in the state of Rio Grande do Norte, Brazil, considering the evidence of anthropic activity along this estuary, resulting in pollution by treated and untreated wastewaters as well as those produced by industry and shrimp farming. The assessment of the environmental status of this estuary was based on physical-chemical parameters, such as granulometry, organic matter and the major (Al, Fe, Mn and P) and minor (Cd, Cr, Cu, Ni, Pb and Zn) elements found in sediment samples. Two collections were made at 12 georeferenced points along the channel of the estuary at different times. Granulometric analysis was carried out and the percentage of organic matter was determined. The sediments were microwave digested using acid digestion and quantitative analyses of the elements Al, Fe, Cd, Cr, Cu, Mn, Ni, P, Pb and Zn were performed by inductively coupled plasma optical emission spectrometry. Sediment analysis followed the methodology proposed by US EPA 3051A for total elements analysis. The small correlation between the organic matter and the elements studied here suggests that they are of geochemical rather than anthropic origin. The analytical results obtained from the bottom sediment samples in the study area show that the concentration of elements was below the reference values for standard shales (Turekian & Wedepohl, 1961) at the vast majority of points analyzed, ruling out a possible contamination by metals